Effect of successive ejaculations on the spermiogram of West African dwarf goats (Capra hircus L.) (2000)
Twenty healthy adult male (bucks) West African dwarf goats (WADG) aged between 2 to 4 years and with a mass of from 16 to 20 kg were used in this study. They were randomly assigned into four groups of five bucks per group. In group A, semen was collected once a week for a period of eight weeks, while in group B semen was collected twice a week for a period of eight weeks, once a day for 21 days in group C, and twice daily at an interval of five hours for 21 days in group D. Live body masses, height at withers, scrotal length and scrotal circumference were not affected by successive ejaculations. The ejaculate volume decreased as the frequency of ejaculations increased, although the decrease was not significant (Group A 0.44±0.07, B 0.41±0.08, C 0.38±0.07 and D 0.36±0.08 ml) while the ejaculate colour was either milky or creamy. Mass sperm movement showed swirling waves and scored 4 in all groups, while the percentage progressive motility ranged between 88.7±3.10 and 94.54±3.00%. Percentage of live spermatozoa (Group A 96.57±2.40, B 96.24±2.53, C 96.10±2.28 and D 96.10±2.50%) was not affected by successive ejaculations although a decrease in sperm concentration was observed as the number of successive ejaculations increased. There was a significant increase (P<0.05) in abnormal spermatozoa as frequency of ejaculation increased.